2024
DOI: 10.1186/s12889-024-17686-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the global prevalence of chronic obstructive pulmonary disease (COPD): a systematic review and meta-analysis

Nadia AL Wachami,
Morad Guennouni,
Younes Iderdar
et al.

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a major public health problem. The present study aims to provide a global and regional estimate of the prevalence of COPD based on spirometry according to the two most widely used diagnostic criteria of COPD: fixed ratio (FR) and lower limit of normal (LLN). Methods We conducted a systematic review of the literature according to PRISMA guidelines. MEDLINE, Web of Sciences, and Scopus databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…We formed the non-ACO group by combining participants from the asthma-only, COPD-only, and non-asthma/COPD groups. In this study, smoking was not considered as a condition to identify COPD [ 38 , 39 ], mainly because while it has been regarded as the best-known and most important risk factor for irreversible airflow obstruction, non-smokers can also develop COPD [ 40 ]. Figure 1 is the flow chart of identifying study population and grouping.…”
Section: Methodsmentioning
confidence: 99%
“…We formed the non-ACO group by combining participants from the asthma-only, COPD-only, and non-asthma/COPD groups. In this study, smoking was not considered as a condition to identify COPD [ 38 , 39 ], mainly because while it has been regarded as the best-known and most important risk factor for irreversible airflow obstruction, non-smokers can also develop COPD [ 40 ]. Figure 1 is the flow chart of identifying study population and grouping.…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have shown that COPD is the third leading cause of death and accounts for 5% of all deaths worldwide each year [ 4 ]. The overall prevalence of COPD in people aged 40 years and older was 12.64% (95% CI 10.75%-14.65%) and 7.38% [ 5 ]. About a quarter of adults over 40 years have moderate airflow limitations, yet most of them are unaware of their conditions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%